Aplysia californica neurons express microinjected neuropeptide genes. - DesGroseillers, L (1987)
Neuropeptide genes are expressed in specific subsets of large polyploid neurons in Aplysia californica. We have defined the transcription initiation sites of three of these neuropeptide genes (the R14, L11, and ELH genes) and determined the nucleotide sequence of the promoter regions. The genes contain the usual eucaryotic promoter signals as well as other structures of potential regulatory importance, including inverted and direct repeats. The L11 and ELH genes, which are otherwise unrelated, have homology in the promoter regions, while the R14 promoter was distinct. When cloned plasmids were microinjected into Aplysia neurons in organ culture, transitions between supercoiled, relaxed circular, and linear DNAs occurred along with ligation into high-molecular-weight species. About 20% of the microinjected neurons expressed the genes. The promoter region of the R14 gene functioned in expression of the microinjected DNA in all cells studied. When both additional 5' and 3' sequences were included, the gene was specifically expressed only in R14, suggesting that the specificity of expression is generated by a multicomponent repression system. Finally, the R14 peptide could be expressed in L11, demonstrating that it is possible to alter the transmitter phenotype of these neurons by introduction of cloned genes.